How to love a Jamaican : stories - Arthurs, Alexia (Ballantine Books, 2018)
Sweeping from close-knit island communities to the streets of New York City and midwestern university towns, these eleven stories form a portrait of a nation, a people, and a way of life. In "Light-Skinned Girls and Kelly Rowlands," an NYU student befriends a fellow Jamaican whose privileged West Coast upbringing has blinded her to the hard realities of race. In "Mash Up Love," a twin's chance sighting of his estranged brother--the prodigal son of the family--stirs up unresolved feelings of resentment. In "Bad Behavior," a couple leave their wild teenage daughter with her grandmother in Jamaica, hoping the old ways will straighten her out. In "Mermaid River," a Jamaican teenage boy is reunited with his mother in New York after eight years apart. In "The Ghost of Jia Yi," a recently murdered student haunts a despairing Jamaican athlete recruited to an Iowa college. And in "Shirley from a Small Place," a world-famous pop star retreats to her mother's big new house in Jamaica, which still holds the power to restore something vital.